The role of the Heritage of Thinkers of the Great step in Spiritual and Moral Education of Student Youth (Journal of Educational Sciences, 2019)
The article deals with the problems of spiritual and moral education of University students. The role of youth as a social group and future professionals who make and will make a great contribution to the prosperity of our country is revealed. The place of heritage of thinkers of the great steppe in education of students of morality in the conditions of spiritual revival is proved. It is a survey article and has a historical character. The thoughts of great scientists and educators of the past were analyzed, which were stated in the works of the great sages of the Kazakh people as Abu Nasr al-Farabi, Yusuf Balasaguni, Mahmut Kashkari, Akhmed Yugineki and Asan Kaigy. For example, analyzing the views of the great al-Farabi, the author emphasizes the philosophical issue of meaning of human life, which is to comprehend happiness. Al-Farabi defines the image of «avirtuous citizen». The purpose of the article is to reveal the importance of morality in human life, which are set out in the works of philosopherds. Examples are of the influence of good and bad traits on self-cognition. The norms of behavior related to the moral qualities of man in the works of thinkers of the great steppe are analyzed. Also, this article analyzes the content of education on the subject of «Selfcognition» in higher school and the use of the works of listed thinkers, offers the author’s methodological examples of teaching.Key words: The Great Steppe, thinkers, the world of wisdom, students, spiritual education, the content of education, teaching methods, works of sages.